2023
DOI: 10.1007/s00428-023-03581-y
|View full text |Cite
|
Sign up to set email alerts
|

Bringing pathology to nanomedicine: a comparison of in vivo toxicity of polymeric nanoparticle carriers with and without chitosan coating

Abstract: Over the last years, there has been an increasing number of proposals for the use of nanomaterials in medicine. The safety of novel technologies must be verified, prior to their clinical application. Pathology has much to contribute towards this end. In this study, we compared the in vivo toxicity effects of poly- (lactic-co-glycolic acid) nanoparticles with and without chitosan shell. Both nanoparticle types were loaded with curcumin. The nanoparticles were assessed in vitro for potential cytotoxicity with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The results showed that the viability of CCA cells treated with 1 mg mL −1 of blank PLGA NPs was above 88% at both incubation times, indicating biocompatibility, as viability above 80% compared to control is considered acceptable. 50 This could potentially be attributed to the inability to compare UA content exclusively in serum-free media, i.e., UA dissolved in 0.25% DMSO, as well as the requirement for UA in PLGA-NPs to diffuse gradually from the NPs. These ndings revealed that UA-PLGA NPs exhibited anti-cancer properties, a slow-released characteristic and an increase in the solubility of UA in water.…”
Section: Drug Loading Encapsulation Efficiency and Release Prolementioning
confidence: 99%
“…The results showed that the viability of CCA cells treated with 1 mg mL −1 of blank PLGA NPs was above 88% at both incubation times, indicating biocompatibility, as viability above 80% compared to control is considered acceptable. 50 This could potentially be attributed to the inability to compare UA content exclusively in serum-free media, i.e., UA dissolved in 0.25% DMSO, as well as the requirement for UA in PLGA-NPs to diffuse gradually from the NPs. These ndings revealed that UA-PLGA NPs exhibited anti-cancer properties, a slow-released characteristic and an increase in the solubility of UA in water.…”
Section: Drug Loading Encapsulation Efficiency and Release Prolementioning
confidence: 99%